Crystallization and preliminary X‐ray diffraction analysis of Lin1840, a putative β‐glucosidase from Listeria innocua. Issue 10 (1st October 2014) - Nakajima, Masahiro; Yoshida, Ryuta; Miyanaga, Akimasa; Taguchi, Hayao
<x xml:space="preserve">Abstract</x> Lin1840 is a putative β‐glucosidase that is predicted to be involved in 1, 2‐β‐glucan metabolism since the lin1839 gene encoding a 1, 2‐β‐oligoglucan phosphorylase and the lin1840 gene are located in the same gene cluster. Here, Lin1840 was crystallized. The crystals of Lin1840 diffracted to beyond 1.8 Å resolution. The crystal belonged to space group I121, with unit‐cell parameters a = 89.75, b = 95.10, c = 215.00 Å, α = 90.00, β = 96.34, γ = 90.00°.